Characteristics and Behavior of Voltage Transient and Inrush Current due to Switching Capacitor Bank - S. Ananwattanaporn; T. Patcharoen; S. Yoomak; Atthapol Ngaopitakkul; C. Pothisarn (My University, 2014)
Capacitor bank system in substation has been a topic of interest in these past few years because of its advantage on system. This paper presents a study on transient signal that occurs when switching capacitor is integrated into the system. The method is based on building a capacitor bank switching experimental setup, which is downscaled from Electricity Generating Authority of Thailand (EGAT) at NongChok substation. This experimental setup is aimed to investigate transient signal in capacitor bank switching that has impact on the power system, such as inrush current and voltage transient. The result shows that switching transient causes an inrush current with high amplitude compared to nominal current. Moreover, an inductor installed in the system can limit inrush current; when inductor size is increased, inrush current will be decreased.
Keywords: Inrush current; Transient (computer programming); SIGNAL (programming language); Power Systems Fault Detection